Location is everything: The hemodynamic effects of REBOA in Zone 1 versus Zone 3 of the aorta. Issue 1 (July 2018) - Tibbits, Emily M.; Hoareau, Guillaume L.; Simon, Meryl A.; Davidson, Anders J.; DeSoucy, Erik S.; Faulconer, E. Robert; DuBose, Joseph J.; Neff, Lucas P.; Grayson, J. Kevin; Williams, Timothy K.; Johnson, M. Austin
Abstract : OBJECTIVES: Resuscitative endovascular balloon occlusion of the aorta (REBOA) is an emerging technology to augment proximal blood pressure during the resuscitation of patients with noncompressible torso hemorrhage. Currently, placement choice, supraceliac (Zone 1) versus infrarenal (Zone 3) aorta, depends on injury patterns, but remains a highly debated topic. We sought to compare the proximal hemodynamic support provided by Zone 1 versus Zone 3 REBOA placement and the degree of hemodynamic instability upon reperfusion following intervention. METHODS: Eighteen anesthetized swine underwent controlled hemorrhage of 25% total blood volume, followed by 45 minutes of Zone 1 REBOA, Zone 3 REBOA, or no intervention (control). They were then resuscitated with shed blood, aortic balloons were deflated, and 5 hours of critical care ensued prior to euthanasia. Physiologic parameters were recorded continuously, and blood was drawn for analysis at specified intervals. Significance was defined as p < 0.05. RESULTS: There were no significant differences between groups at baseline or during the initial 30 minutes of hemorrhage. During the intervention period, average proximal MAP was significantly greater in Zone 1 animals when compared with Zone 3 animals (127.9 ± 1.3 vs. 53.4 ± 1.1 mm Hg) and greater in Zone 3 animals when compared with control animals (42.9 ± 0.9 mm Hg). Lactate concentrations were significantly higher in Zone 1 animals (9.6 ± 0.4 mmol/L) when compared with Zone 3 animals (5.1 ± 0.3 mmol/L) and control animals (4.2 ± 0.8 mmol/L). CONCLUSIONS: In our swine model of hemorrhagic shock, Zone 3 REBOA provided minimal proximal hemodynamic support when compared with Zone 1 REBOA, albeit with less ischemic burden and instability upon reperfusion. In cases of impending hemodynamic collapse, Zone 1 REBOA placement may be more efficacious regardless of injury pattern, whereas Zone 3 should be reserved only for relatively stable patients with ongoing distal hemorrhage.